Redondovirius-associated periodontitis in people with poor oral hygiene: a cross-sectional study - Mohebbi, Alireza; Donyavi, Zakiyeh; Mamizadeh, Zoleikha; Khanaliha, Khadijeh; Emtiazi, Nikoo; Kiani, Seyed Jalal; Donyavi, Tahereh; Shadab, Alireza; Babaei, Roghayeh; Bokharaei-Salim, Farah (Frontiers in Oral Health, 2025)
BackgroundThis study aimed to investigate the prevalence of recently emerged members of the Redondoviridae family (ReDoVs) in individuals with periodontitis.MethodsThis study involved real-world data from 230 participants, 115 with chronic periodontitis and an independent population consisting of 115 participants with oral hygiene habits selected from the refferals, and approved by the experts from October 2023 to May 2024. Demographic, health-related, and behavioral data were collected. Gingival samples were analyzed for ReDoVs using polymerase chain reaction (PCR), followed by sequencing and phylogenetic analysis.ResultsReDoVs were detected in 51.30% of the periodontitis group and 21.74% of the other groups with oral hygiene habits (p < 0.0001). ReDoV presence was associated with a lack of teeth-brushing habits (p < 0.05). Furthermore, flossing was negatively correlated with reduced ReDoV genomes (r = –0.20, p = 0.03).ConclusionsReDoVs and periodontitis were associated with adults with poor dental hygiene. This supports a possible multifactorial and complex interaction between the presence of ReDoVs and periodontitis. Also, the findings of this study highlight that poor oral hygiene increases the likelihood of ReDoV presence and suggests that factors such as flossing are predictors of ReDoV infections.